Plate tectonics - Le Pichon, Xavier; Francheteau, Jean; Bonnin, Jean (Developments in geotectonics, 1973)
Developments in Geotectonics, 6: Plate Tectonics focuses on the exposition of the plate-tectonics hypothesis, as well as plate boundaries, stratification, and kinematics. The book first offers information on the rheological stratification of the mantle and kinematics of relative movements. Topics include lithosphere, asthenosphere, kinematics of finite motions, measurements of instantaneous movements, and worldwide kinematic pattern. The text then ponders on movements relative to a frame external to the plates and processes at accreting plate boundaries. Discussions focus on reference frames,